O-014 Technical and clinical outcomes in distal occlusion thrombectomy by frontline technique – a multicenter study. (23rd July 2022) - Alawieh, A; Chalhoub, R; Al-Kasab, S; Pullmann, D; Jabbour, P; Psychogios, M; Starke, R; Arthur, A; Fargen, K; DeLeacy, R; Kan, P; Dumont, T; et al.
Abstract : Background: Endovascular thrombectomy (EVT) is the standard of care for proximal large vessel occlusion (LVO) stroke. Due to the high effect size of EVT, neurointerventionalists have expanded the indications of EVT to include more distal occlusions. Data on technical and clinical outcome in distal vessel occlusions (DVOs) remain limited. We evaluated technical and clinical outcomes after EVT in distal occlusion stroke while comparing different frontline thrombectomy techniques. Methods: We report an international multicenter retrospective study of patients, 18 years or older, undergoing EVT for ischemic stroke at 32 centers between 01/2015 and 12/2021. Patients were divided into proximal occlusions(ICA/M1/Vertebrobasilar), medium vessel occlusions (M2, A1, P1) or isolated distal vessel occlusions (M3, M4, A2, A3, P2/3) and categorized by the thrombectomy technique. Primary outcome was a good functional outcome(mRS 0–2) at 90 days and compared between different techniques. Secondary outcomes included successful recanalization, procedure time, thrombectomy attempts, post-procedural hemorrhage and mortality. Multivariate logistic regressions were used to evaluate the impact of technical variables including procedure time, attempts, and frontline technique on clinical outcomes. Propensity score matching was used to compare outcome in patients with DVO treated with aspiration versus stent retriever as frontline approach. Results: We included 7, 477 patients including 5977 proximal occlusions and 213 distal occlusions. Distal location did not independently predict good functional outcome at 90 days compared to proximal when baseline covariates were accounted for (p=0.467). In distal occlusions, successful recanalization was an independent predictor of good outcome at 90 days (aOR=5.11, p<0.05) irrespective of frontline technique. Younger age, use of bridging therapy and lower admission NIHSS were also predictors of good outcome. Procedure time less than 1 hr or thrombectomy attempts less than 3 were independent predictors of 90-day good outcomes in the DVO cohort irrespective of technique (aOR = 4.5 and 2.3 respectively, p < 0.05). There were no differences in technical or clinical outcomes in a matched cohort of aspiration versus stent-retriever in the DVO group (p>0.5). Rates of hemorrhage and good outcome showed an exponential relationship to procedural metrics, and were more dependent on procedure time in the aspiration group compared to the number of attempts in the stent-retriever group. Conclusions: Clinical outcomes following EVT for DVO are comparable to those in LVOs with similar baseline covariates with no differences between the different frontline techniques. The golden hour or 3-pass rules in LVO thrombectomy still apply to DVO thrombectomy. Different frontline techniques may exhibit different futility metrics; SR thrombectomy was more influenced by more attempts whereas aspiration outcomes were more dependent on procedure time. Disclosures: A. Alawieh: None. R. Chalhoub: None. S. Al-Kasab: None. D. Pullmann: None. P. Jabbour: 2; C; Medtronic, MicroVention, Cerus Endovascular, and Balt. M. Psychogios: 1; C; Phenox, Stryker, and Siemen. R. Starke: 1; C; Medtronic. 2; C; Penumbra, Abbott, Medtronic, InNeuroCo and Cerenovus. A. Arthur: 2; C; Balt, Johnson and Johnson, Leica, Medtronic, MicroVention, Penumbra, Scientia, Siemens, and Stryker. K. Fargen: None. R. DeLeacy: None. P. Kan: 2; C; Stryker and Cerenovus. T. Dumont: None. A. Rai: None. R. Crosa: None. S. Tjoumakaris: None. I. Maier: None. N. Goyal: None. S. Wolfe: None. C. Cawley: None. J. Osbun: None. B. Howard: None. L. Dimisko: None. H. Saad: None. C. Ogilvey: None. W. Crowley: None. J. Mascitelli: None. I. Fragata: None. M. Levitt: None. A. Shaban: None. J. Kim: None. S. Yoshimura: None. A. Polifka: None. R. Williamson: None. B. Gory: None. M. Mokin: None. M. Moss: None. M. Park: None. J. Grossberg: None. A. Spiotta: 1; C; Penumbra, Pulsar Vascular, MicroVention, and Stryker. 2; C; Penumbra, MicroVention, and PulsarVascular.